The overlooked soil organic carbon stocks in African mixed crop-livestock farming systems: a case study from Zimbabwe - (:unkn) unknown (My University, 2024)
Soil organic carbon (SOC) is instrumental in the global carbon cycle and in many functions relating to soil fertility. Land-use change such as the conversion of forests or grazing lands and an inappropriate management in many smallholder farming systems across sub-Saharan Africa (SSA) have led to an important loss of SOC at plot, farm, and regional scales. The accurate estimation of current SOC stocks is crucial if effective land management practices that encourage increase in SOC in the soil are to be promoted and adopted. The objectives of this study in Murehwa smallholder communal area, Zimbabwe, were to quantify SOC stocks under different land uses and soil types and SOC stocks at landscape scale, to assess the impact of historical management on SOC in croplands, and to compare measured SOC stocks with publicly available geodata namely Africa Soil Information Service (AfSis) to evaluate its reliability and applicability. Soil sampling was carried out across three villages on three main soil types from five identified land use types: croplands, gardens, fallow fields, grasslands, and forest woodlands at two depths 0 – 20 cm and 20 – 40 cm. Highest SOC stocks were found in grasslands followed by gardens, with SOC stocks of 31.7 Mg C ha-1 and 28.5 Mg C ha-1, respectively. In croplands, particularly under sandy soils, average stocks were higher on fields closest to homesteads than on fields further away. The results indicate a much lower SOC stock in AfSiS compared to measured values, suggesting there is need for caution when interpreting the geospatial data because of uncertainties that arise from using these methods. It is necessary to carry out ground-truthing if we are to accurately identify SOC stocks hot spots and assess the potential impact of land use change.
Keywords: African Research